Problems of Formation of Tolerance in Modern Europe: International Legal Aspect - Vadim Rafailovich Atnashev (Управленческое консультирование, 2018)
The article basing on the international law and international standards considers issues of spreading intolerance, xenophobia and racial discrimination. The latter evils and related intolerance often provoke radicalism and extremism in the modern world, trigger separatism and threaten the stability of many European countries. The author compares the situations in France, Germany, Great Britain, including issues of the immigration and citizenship policies, measures of immigrant integration.